ASSOCIATION BETWEEN IT-HOSPITAL MORTALITY AND NON-SURGICAL COMPLICATIONS AFTER OPERATION IN LOWER LIMB AMPUTATION DUE TO PERIPHERAL ARTERY DISEASE - Макаров, Денис Николаевич; Васильченко, Елена Михайловна (Medicine in Kuzbass, 2018)
Objective – to investigate the structure of non-surgical complications after operation, define its effect on in-hospital mortality in lower limb amputations in patients with peripheral artery disease.Materials. A retrospective analysis of 656 case records of patients with peripheral artery disease that undergone lower limb amputation was performed. Identification of independent factors that influence mortality rate was performed using binary logit regression model.Results. The risk of in-hospital mortality increases 33,7-fold in case of development of acute kidney failure, in case of thromboembolia of the pulmonary artery it increases 17,6-fold, pulmonary edema – 14,3-fold increase, and myocardial infarction – 6,3-fold increase.Conclusions. Non-surgical complications after operation following lower limb amputation in patients with obliterative arterial disease developed in 24,8 % of cases. Despite psychiatric disorders developed more often than other complications, they did not influence the in-hospital mortality. Acute kidney failure, thromboembolia of the pulmonary artery, pulmonary edema and myocardial infarction that developed in the postoperative period are the independent predictors of in-hospital mortality in limb amputation in patients with peripheral artery disease.
Keywords: lower limb ischemia; mortality; amputation; atherosclerosis; postoperative complications